2011
DOI: 10.3329/jsr.v3i2.6557
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Cancer (HeLa) Cell Killing Efficacy of Aqueous Garlic (<i>Allium sativum</i>) Extract

Abstract: Garlic (Allium sativum) is a herb that is used mainly as a food in many countries for its medicinal properties since ancient times. It enhances immune functions and has antibacterial, antifungal, antivirus and anticancer activities. Organosulfur compounds originating from garlic inhibit carcinogen activation. In this study we prepared aqueous garlic extract (AGE) and its in vitro application to cancer (HeLa) cell line was performed to observe the cancer cell killing efficacy. Different concentrations of AGE li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Recently we reported the cytotoxicity effect of aqueous garlic extract (AGE) on cancer cell [26] and further we are very interested to apply these nanomaterials in cancer (HeLa cell) treatment. Fig.4.…”
Section: Heating Capabilitymentioning
confidence: 99%
“…Recently we reported the cytotoxicity effect of aqueous garlic extract (AGE) on cancer cell [26] and further we are very interested to apply these nanomaterials in cancer (HeLa cell) treatment. Fig.4.…”
Section: Heating Capabilitymentioning
confidence: 99%
“…Thirdly, the molecular mechanism involved in the anticancer activity of SLs, in particular, the SL-thiols reaction, the effect of SLs on cell signaling pathways such as nuclear transcription factor-kappaB (NF-kappaB) and mitogen-activated protein kinases (MAPK). [36][37][38][39] Biophytum sensitivum An alcoholic extract of Biophytum sensitivum (Oxalidaceae) leaves was also found to be cytotoxic towards L929 cells in culture at a concentration of 0.1 mg/ml. The extract was 100% toxic at a concentration of 0.5 mg/ml to Dalton's lymphoma ascites (DLA) and Ehrlich ascites carcinoma (EAC) cells.…”
Section: Allium Sativummentioning
confidence: 99%
“…Eruboside-B exhibited in-vitro cytotoxic activity against several cancer cell lines with the following ED 50 values (μg/mL): BC1 human breast cancer (3.6 μg/mL) Lu1 human lung cancer (1 μg/mL), Col2 human colon cancer (1 μg/ mL), KB human oral epidermoid cancer (12.7 μg/ mL), KB-V (+VLB) drug-resistant KB assessed in the presence of vinblastine (9 μg/mL) and KB-V (−VLB) and drug-resistant KB assessed in the absence of vinblastine (8.7 μg/mL). The results of in-vitro studies revealed that 95 % of HeLa cervical cancer cells were killed at a dose of 500 μL aqueous garlic extract, whereas about 92, 87, 60 and 24 % cancer cells were killed at doses of 400, 300, 200 or 100 μL of, respectively, Islam et al ( 2011 ).…”
Section: In-vitro Studiesmentioning
confidence: 99%